Drug‐induced photosensitivity: new insights into pathomechanisms and clinical variation through basic and applied science. (1st April 2017) - Khandpur, S.; Porter, R.M.; Boulton, S.J.; Anstey, A.
Summary: Drug‐induced photosensitivity occurs when a drug is capable of absorbing radiation from the sun (usually ultraviolet A) leading to chemical reactions that cause cellular damage (phototoxicity) or, more rarely, form photoallergens (photoallergy). The manifestation varies considerably in presentation and severity from mild pain to severe blistering. Despite screening strategies and guidelines in place to predict photoreactive drugs during development there are still new drugs coming onto the market that cause photosensitivity. Thus, there is a continuing need for dermatologists to be aware of the different forms of presentation and the culprit drugs. Management usually involves photoprotection and cessation of drug treatment. However, there are always cases where the culprit drug is indispensable. The reason why some patients are susceptible while others remain asymptomatic is not known. A potential mechanism for the phototoxic reactions is the generation of reactive oxygen species (ROS), and there are a number of reasons why some patients might be less able to cope with enhanced levels of ROS.